Peran Guru Pendidikan Agama Islam dalam Meningkatkan Kualitas Belajar Adab di Era Digital Peserta Didik Kelas X SMA Hidayatullah Bontang Tahun Pelajaran 2023/2024 - Fahrudin (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2025)
This study aims to explore the role of PAI teachers in improving the quality of adab learning and adab coaching. The learning of adab aims to create individuals who obey Allah in their daily lives, interact well in the environment, and follow Islamic guidelines. The approach used is descriptive qualitative research by collecting data through observation, interviews, and document reviews. The results of the study show that the role of teachers includes supervision of daily activities, mentoring, guidance, and direct direction of adab learning. Teachers play a role in implementing adab activities, getting used to adab in daily life, and supporting activities in accordance with Islamic sharia to ensure a thorough understanding of adab. Other important factors include the expertise of teachers, a routine daily learning schedule, and textbooks as a learning guideline for students at Hidayatullah High School. The ultimate goal is to produce students who have faith, noble character, and become role models in society. Based on this, it is concluded that the important role of PAI teachers in improving the quality of student manners learning. Teachers play a role in supervising, guiding, and providing direction in the application of daily manners in accordance with Islamic guidelines. Using a descriptive qualitative approach through observation, interviews, and document studies, the results of the study show that learning adab is effective through habituation of adab in daily life and activities in accordance with Islamic law. This is expected to create students who obey Allah and have.